2014
DOI: 10.1128/aac.02183-13
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate-Containing Polyethylene Glycol Polymers Prevent Lethal Sepsis by Multidrug-Resistant Pathogens

Abstract: Antibiotic resistance among highly pathogenic strains of bacteria and fungi is a growing concern in the face of the ability to sustain life during critical illness with advancing medical interventions. The longer patients remain critically ill, the more likely they are to become colonized by multidrug-resistant (MDR) pathogens. The human gastrointestinal tract is the primary site of colonization of many MDR pathogens and is a major source of life-threatening infections due to these microorganisms. Eradication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 35 publications
3
64
0
2
Order By: Relevance
“…Further, microbes alter their virulence in response to both the internal host environment (availability of phosphate) and treatments in critically ill patients (opiates) [223][224][225]. Bacteria in pre-clinical models of sepsis can be tricked into "believing" that the host environment is non-toxic, preventing the development of virulence factors that would ordinarily occur in sepsis, leading to survival advantage in septic rodents [226]. Microbes also possess the capacity for quorum sensing in which individual cells can work together to collectively respond to the environment [227,228].…”
Section: Basic/translational Science What Mechanisms Underlie Sepsis-mentioning
confidence: 99%
“…Further, microbes alter their virulence in response to both the internal host environment (availability of phosphate) and treatments in critically ill patients (opiates) [223][224][225]. Bacteria in pre-clinical models of sepsis can be tricked into "believing" that the host environment is non-toxic, preventing the development of virulence factors that would ordinarily occur in sepsis, leading to survival advantage in septic rodents [226]. Microbes also possess the capacity for quorum sensing in which individual cells can work together to collectively respond to the environment [227,228].…”
Section: Basic/translational Science What Mechanisms Underlie Sepsis-mentioning
confidence: 99%
“…The use of non-microbicidal drugs to create microenvironmental conditions that suppress the virulence of pathogens is an attractive strategy to minimize the negative consequences of intestinal microbiome disruption caused by antibiotic use [14,28,29,32,33]. It has been shown previously that phosphate is depleted in the intestinal tract following surgical injury, that this depletion is a major "cue" that triggers bactericidal virulence, and that the maintenance of luminal phosphate abundance in the gut prevents virulence expression [12,14,32,33].…”
Section: Perspectivementioning
confidence: 99%
“…It has been shown previously that phosphate is depleted in the intestinal tract following surgical injury, that this depletion is a major "cue" that triggers bactericidal virulence, and that the maintenance of luminal phosphate abundance in the gut prevents virulence expression [12,14,32,33]. Since inorganic phosphate is not a suitable agent for phosphate delivery to the site of host-pathogen interaction, because it is readily absorbed in the small intestine, other ways must be found [32].…”
Section: Perspectivementioning
confidence: 99%
“…Ackland et al reported that lowmolecular-weight PEG (200e400 Da) reduced inflammatory cytokine expression, pyrexia, and mortality in both LPS and zymosan models of sepsis [17]. Zaborin et al demonstrated that phosphorylated PEG prevents lethal sepsis in mice inoculated with multiple highly virulent pathogenic organisms from hospitalized patients [18]. Based on the biological effect of each LYZ and PEG, we hypothesized that PEGylated LYZ (PEG-LYZ), the combined form of LYZ and PEG, could give synergistic effect on the treatment of sepsis.…”
Section: Introductionmentioning
confidence: 98%